Canine ex vivo tarsal arthrodesis: fixation by using a new bone tissue glue - Lundin, Tobias Per Otto; Pujari-Palmer, Michael; Svensson, Gustaf; Höglund, Odd Viking (Frontiers in Veterinary Science, 2023)
Introduction: Arthrodesis, performed as a salvage surgical procedure to treat intractable joint conditions in dogs and cats, is associated with a high incidence of complications intra and postoperative. Proving the need for improved and new techniques in arthrodesis surgery. Adding a new resorbable bone glue to the arthrodesis could potentially add fixation strength and lower complications.The objectives of this experimental ex vivo biomechanical study were therefore to develop a biomechanical test model of partial tarsal arthrodesis and to determine whether the new resorbable bone glue (phosphoserine modified cement) produced measurable fixation strength in canine calcaneoquartal arthrodesis, without orthopedic implants.Methods: Four biomechanical test models with a total of 35 canine tarsal joints were used. Soft tissues were dissected to 4 different test models with variable contributions from soft tissues. The calcaneoquartal joint was prepared as in vivo arthrodesis and the glue was applied to joint surfaces as a liquid/putty (0.4 cc). After curing for 24 hours, a shear force was applied to the joint (1 mm per minute) and the failure strength was recorded.Results: Calcaneoquartal joints, where all soft tissues had been completely resected and fixated with glue (1-1.5 cm 2 joint surface), withstood 2-5 mm of displacement and an average of 100 ± 58 N/cm 2 of shear force (Model 1). Similar adhesive fixation strengths were obtained in Model 2 and 3 with increasing contributions from soft tissues (80 ±44 and 63 ±23 N/cm 2 , p = 0.39, ANOVA).The developed biomechanical model was sensitive enough to measure differences in fixation strengths between different glue formulations. The average fixation strength (60-100 N/cm 2 ) should be strong enough to support short-term load bearing in medium sized canines (20 kg). The developed cadaver biomechanical test model is of potential use for other arthrodesis studies. The new resorbable glue can potentially contribute to stability at arthrodesis surgery, acting as a complement to today's standard fixation, metal implants.